EXPERIENCIAS DE FLUJO EN EL APRENDIZAJE DE LAS MATEMÁTICAS - Medina, Ana Belen Montoro; Cuadra, Francisco Gil; Carretero, Maria Francisca Moreno (European Scientific Journal, ESJ, 2013)
When students experience flow within academic tasks, their performance and their engagement with the subject increases. Flow (states of deep concentration and enjoyment) depends on the person, the task and the environment in which it is carried out. This study intends to know the kind of activities that provide flow in a sample of 121 university students. For this purpose, the researchers use a questionnaire and an interview. The data analysis suggests that the main indicators to identify flow experiences are deep concentration, lost track of time and enjoyment. It also shows that having great mathematical skills is not necessary to experience flow with activities; and that the main flow activity in mathematics involves problem solving, regardless of the chosen degree and previous experience in this field.